KLASIFIKASI SISTEM PEMERINTAHAN (Perspektif Pemerintahan Modern Kekinian) - Anangkota, Muliadi (CosmoGov: Jurnal Ilmu Pemerintahan, 2017)
The system of government that practiced in many countries today tend to experience the changes. Some countries have special characteristics of its own in the event of the existence of the country. Characteristic of the country one is to have a system of government. This article is the result of the study the theoretical concept about the classification system of government that until now still practiced in various countries. Study method using the methods of the study of literature with descriptive approach. Study results showed that in the classification of the system of government is currently consists of the parliamentary system, presidential, mixture and a referendum. The system of government to be one of the determining factors in the sustainability of the statehood. On the other the government will run effectively and normal where the old system that is selected and used in accordance with the social political conditions character state.gb777